2009
DOI: 10.1021/ef800706c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Asphaltene Dispersants on Aggregate Size Distribution and Growth

Abstract: A crude oil system can become unstable because of changes in hydrocarbon composition, pressure, or temperature during normal production from the reservoir or during commingling with dissimilar crude oils. These changes can generate asphaltene particles that can result in significant production and refining problems. The generation of these particles is a two-step process: phase separation and asphaltene particle growth. Phase separation occurs when nanosize asphaltene particles from the crude oil precipitate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
87
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 34 publications
3
87
0
6
Order By: Relevance
“…Although both DBSA and OP [2] favored the formation of filamentary asphaltene flocculates, the mechanism by which these filaments formed was very different. In addition to the strong acid-base interaction between protonated asphaltenes (i.e., AH + ) and DBS À molecules, which was in accord with previous studies [1,3,[4][5][6][7][8], an additional electrostatic attraction was found between AH + -DBS À ion pairs. The latter was responsible for (i) the formation of very large and compact asphaltene flocculates, and (ii) the binding of these flocculates in series (generating long filaments) or in parallel (generating lateral ramifications).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although both DBSA and OP [2] favored the formation of filamentary asphaltene flocculates, the mechanism by which these filaments formed was very different. In addition to the strong acid-base interaction between protonated asphaltenes (i.e., AH + ) and DBS À molecules, which was in accord with previous studies [1,3,[4][5][6][7][8], an additional electrostatic attraction was found between AH + -DBS À ion pairs. The latter was responsible for (i) the formation of very large and compact asphaltene flocculates, and (ii) the binding of these flocculates in series (generating long filaments) or in parallel (generating lateral ramifications).…”
Section: Discussionsupporting
confidence: 91%
“…Asphaltene interactions with DBSA are significantly stronger than with alkylphenols since acid-base interactions are stronger than hydrogen bonding [1,3,[4][5][6][7][8]. The acidic ASO 3 H groups of DBSA can protonate the basic groups of asphaltenes containing heteroatoms such as Nitrogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong organic acids, in particular DBSA, are found to work by attacking heteroatomic sites in asphaltene molecules Hashmi and Firoozabadi 2013). The resultant acid-base interactions along the long-chain carbon tails of DBSA form a solvation shell around the asphaltene molecules, thereby dissolving them (Leon et al 1999;Rogel and Leon 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A non-exhaustive list includes automatic titration, [23][24][25] optical microscopy, 23 dynamic turbidity, 23 particle size distribution, 23 SARA analysis, 26 Vapor Pressure Osmometry (VPO), 27 Gel Permeation Chromatography (GPC), 28 etc. These techniques are used to study the effect of inhibitors/dispersants on the precipitation onset, flocculation, settling and aggregate size distribution of asphaltenes.…”
Section: Introductionmentioning
confidence: 99%